2015
DOI: 10.1016/j.cortex.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Visual processing of words in a patient with visual form agnosia: A behavioural and fMRI study

Abstract: Patient D.F. has a profound and enduring visual form agnosia due to a carbon monoxide poisoning episode suffered in 1988. Her inability to distinguish simple geometric shapes or single alphanumeric characters can be attributed to a bilateral loss of cortical area LO, a loss that has been well established through structural and functional fMRI. Yet despite this severe perceptual deficit, D.F. is able to "guess" remarkably well the identity of whole words. This paradoxical finding, which we were able to replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…A picture consisted of two simple geometric figures. Previous studies have used geometric figure discrimination to measure visual form perception (e.g., Efron, 1969 ; Milner et al, 1991 ; Cavina-Pratesi et al, 2015 ). The four line pictures were presented simultaneously for 400 ms. Each picture had horizontal and vertical visual angles of 2.8°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A picture consisted of two simple geometric figures. Previous studies have used geometric figure discrimination to measure visual form perception (e.g., Efron, 1969 ; Milner et al, 1991 ; Cavina-Pratesi et al, 2015 ). The four line pictures were presented simultaneously for 400 ms. Each picture had horizontal and vertical visual angles of 2.8°.…”
Section: Methodsmentioning
confidence: 99%
“…Tibber et al ( 2012 ) showed that the sensitivity to the orientations of two clusters of Gabor blobs could predict math abilities, but the sensitivity to size and density could not. The visual perception tasks used in these studies, however, were mostly focused on size, color, or brightness, which are different from visual form processing (e.g., Milner et al, 1991 ; Cavina-Pratesi et al, 2015 ). Thus, these tasks might not fully measure visual form processing.…”
Section: Introductionmentioning
confidence: 99%
“…Third, patients who suffer from visual form agnosia had difficulties in the numbers and mathematical signs (Milner et al, 1991;Cavina-Pratesi et al, 2015). For example, patient DF suffers from a permanent visual form agnosia, so she cannot distinguish single alphanumeric characters or simple geometric shapes.…”
Section: Visual Perception Hypothesis For the Association Between Num...mentioning
confidence: 99%
“…Besides, such patients have reduced control over the accuracy of object recognition [2]. Visual object agnosia is likely to be accompanied by impaired recognition of familiar faces (prosopagnosia), less often letters and words ("pure" alexia without agraphia) [3,11].…”
Section: Introductionmentioning
confidence: 99%